Chronic Viral Hepatitis May Diminish The Gains Of HIV Antiretroviral Therapy In Sub-Saharan Africa - Cooper, Curtis L.; Mills, Edward; Wabwire, Ben O.; Ford, Nathan; Olupot, Peter Olupot (International Journal of Infectious Disease, 2009)
There is a heavy burden of HIV–hepatitis B virus (HBV) and HIV–hepatitis C virus (HCV) co-infection in many regions of the developing world. An often unmentioned illness, issues of poverty, socio-economic status, nutrition, access to medical care, and mistrust of Western-style medicine conspire to reduce the opportunity to receive clinical work-up and treatment for chronic viral hepatitis. We discuss key issues specific to the treatment of viral hepatitis and obstacles to success with this endeavor in the context of HIV co-infection in Africa. We predict that provision of viral hepatitis antiviral therapy will become a more pressing issue as more HIV-infected patients receive lifesaving combination antiretroviral therapy only to succumb thereafter from viral hepatitis-induced liver disease. Given the lessons learned from combination antiretroviral rollout in sub-Saharan Africa, establishing expertise and infrastructure for viral hepatitis care and antiviral therapy is relevant. Failure to act now may diminish the milestones and the gains made with antiretroviral therapy in the developing world.
Keywords: HBV; HCV; HIV; Antiretroviral; Developing world